Qualitative Content Analysis Of Health Crisis Information On The Ministry Of Health Website - Salsabila Fadhilah Putri; Azwar (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Indonesia faces various challenges in the effective dissemination of health crisis information to the public, especially in the context of improving preparedness for disasters and health emergencies. This study aims to analyze the qualitative content of health crisis information presented in the official website of the Ministry of health of the Republic of Indonesia, particularly through the article “Disaster Preparedness Tips” published by the Health Crisis Center. In this study using the qualitative content analysis method Krippendorff (2018) and the concept of Digital Government from Cordella and Paletti (2019), this study examines how health crisis messages are constructed, structured, and communicated digitally to the community. The results showed that the construction of the message in the article focuses on two main functions, namely early warning and public health education and socialization. The message is informative and instructive, emphasizing on increasing risk awareness, disease prevention, and the implementation of clean and healthy living behavior during and after disasters such as floods and rainy seasons. The findings illustrate the government's role as a credible provider of digital public information and efforts to build public value through improved health literacy and community preparedness. However, the communication used is still one-way (information sharing) and has not accommodated interactive public participation. Overall, the Health Crisis Center website has functioned as an informative and educative disaster digital communication medium, although it needs to be strengthened in the aspects of interactivity and collaboration to be more in line with the principles of inclusive and participatory digital governance.